Marfan Syndrome and Pregnancy: Maternal and Neonatal Outcomes. Issue 1 (March 2015) - Curry, R.A.; Gelson, E.; Swan, L.; Dob, D.; Babu-Narayan, S.V.; Gatzoulis, M.A.; Steer, P.J.; Johnson, M.R.
Abstract : ( BJOG . 2014;121(5):610–617)